PENGARUH KUALITAS PELAYANAN DAN WORD OF MOUTH (WOM) TERHADAP KEPUASAN PELANGGAN PADA USAHA RB RUMAH KITA DI DESA MANUBURA KECAMATAN NELLE KABUPATEN SIKKA - Yoseph Ardiano Ruwe; Antonius Phillipus K.Gheta; Dimas Realino (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2026)
The purpose of this study is to examine how customer satisfaction at RB Rumah Kita, which is situated in Manubura Village, Nelle District, Sikka Regency, is impacted by service quality and word-of-mouth (WOM). This study used a survey method with a quantitative approach. Customers of RB Rumah Kita made up the study's population, and the sample was chosen using a suitable sampling technique in compliance with quantitative research protocols. Multiple linear regression analysis was used to assess the data that was gathered via surveys. The study found that service quality had a favorable impact on customer satisfaction. In addition, word of mouth (WOM) was discovered to have a favorable and considerable impact on consumer satisfaction. Simultaneously, these two characteristics help to boost customer satisfaction at RB Rumah Kita. This research implies that the higher the level of customer satisfaction, the better the service quality and the stronger the positive word-of-mouth. This study makes practical recommendations for business owners seeking to improve service tactics and generate positive word-of-mouth in order to increase business competitiveness. Furthermore, this study makes theoretical contributions to the growth of marketing management studies, namely the relationship between service quality, word-of-mouth, and customer happiness.